2022
DOI: 10.26508/lsa.202201455
|View full text |Cite
|
Sign up to set email alerts
|

Protein and RNA ADP-ribosylation detection is influenced by sample preparation and reagents used

Abstract: The modification of substrates with ADP-ribose (ADPr) is important in, for example, antiviral immunity and cancer. Recently, several reagents were developed to detect ADP-ribosylation; however, it is unknown whether they recognise ADPr, specific amino acid–ADPr linkages, or ADPr with the surrounding protein backbone. We first optimised methods to prepare extracts containing ADPr–proteins and observe that depending on the amino acid modified, the modification is heatlabile. We tested the reactivity of available… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 71 publications
4
13
0
Order By: Relevance
“…We have integrated these protocols with our highly sensitive and specific SpyTag antibodies 17 as well as proteomics technology. Our results are consistent with recent reports showing that boiling the sample causes significant losses of the ADP-ribose signal 20 , 38 . While heating at 60 °C in a non-denaturing lysis buffer, which requires PARP inhibitor to prevent post-lysis ADPr, has been proposed as an alternative to boiling 38 , a key feature of our western blotting protocol is the avoidance of heating samples.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have integrated these protocols with our highly sensitive and specific SpyTag antibodies 17 as well as proteomics technology. Our results are consistent with recent reports showing that boiling the sample causes significant losses of the ADP-ribose signal 20 , 38 . While heating at 60 °C in a non-denaturing lysis buffer, which requires PARP inhibitor to prevent post-lysis ADPr, has been proposed as an alternative to boiling 38 , a key feature of our western blotting protocol is the avoidance of heating samples.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, protein extraction and immunoblotting efficiency, assessed via ponceau, PARP1, GAPDH and H3 staining, was not affected by the omission of boiling. Non-denaturing lysis conditions can result in the post-lysis activity of enzymes, including PARP1 11 , 38 , requiring the use of inhibitors. Crucially, 4% SDS at room temperature is sufficient to completely inactivate PARP1 and PARG (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has demonstrated that ADPr thermolability and pH stability can vary based on the linkage type . These are critical parameters to consider when preparing and analyzing ADPr samples.…”
Section: Resultsmentioning
confidence: 99%
“…In all transfections, the total amount of DNA added was supplemented to 500 ng with an empty cloning vector, pQCXIP (Clontech, Mountain View, CA, USA). Detection of ADP-ribosylation has been shown to be highly dependent on sample conditions [ 38 ], and we have observed that the edges of multiwell plates give less consistent signal than the middle of plates. As a result, only the central eight wells of any given plate were used for transfection.…”
Section: Methodsmentioning
confidence: 96%